Floristic composition in the ruderal areas of Southeast Anatolia, Turkey (Bangladesh Journal of Plant Taxonomy, 2021)
Survey on the floral diversity is an important activity to evaluate the existing flora. This study was carried out from 2018 to 2020 to investigate the flora existing in the roadside and ruderal areas between Şanlıurfa and Bozova, nearby Euphrates river. A total of 200 taxa belonging to 138 genera and 41 families were determined. 9 of these taxa are endemic to Turkey. Among the plants identified, there are 5 geophytes, 1 parasite and 14 cultivated plants. The families with the most taxa are Fabaceae (47), Asteraceae (30), Lamiaceae (15), Poaceae (13) and Brassicaceae (7). The genera with the dominant taxa are; Astragalus (7), Medicago (7), Trigonella (7), Vicia (5) and Trifolium (5). In distribution of plants in the study area, the Irano-Turanian elements (38%, 75 taxa) ranks first, Mediterranean elements second (15%, 30 taxa) and Euro-Siberian elements third (1%, 3). The botanical- and vernacular names and habit categories of the recorded plant taxa are cited systematically. Threats to these plants and possible conservation strategies are also discussed briefly.Bangladesh J. Plant Taxon. 28(1): 241-256, 2021 (June)